The relationship between energy and socio-economic development in the Southern and Eastern Mediterranean - Emmanuel Bergasse; Wojciech Paczynski; Marek Dabrowski; Luc De Wulf (Center for Social and Economic Research (CASE), 2013)
This report aims to identify, explain and detail the links and interactions in Southern and Eastern Mediterranean countries (SEMCs) between energy supply and demand and socio-economic development, as well as the potential role of energy supply and demand policies on both. Another related aim is to identify and analyse, in a quantitative and qualitative way, the changing role of energy (both demand and supply) in southern Mediterranean economies, focusing on its positive and negative impact on socio-economic development. This report investigates in particular: * The most important channels through which resource wealth can contribute to or hamper economic and social development in the analysed region; * Mechanisms and channels of relations between energy supply and demand policies and economic and social development. The burdens of energy subsidies and 'oil syndrome' are of particular relevance for the region. An integrated socio-economic development and energy policy scenario approach showing the potential benefits and synergies within countries and the region is developed in the final part of the report.
Keywords: A10; 330; Southern Mediterranean Countries (SEMCs); socio-economic development; energy demand; energy efficiency; energy prices; energy subsidies; resource curse; Dutch disease; oil syndrome; energy policy; socio-economic development strategy; targeted subsidies; integrated energy strategy; energy efficiency action plans; renewable energy action plans; climate policy; regional Mediterranean energy cooperation; Arab Spring; Energiekonsum; Energie; Nachfrage; Energiepolitik; Makroökonomischer Einfluss; Mittelmeerraum